The incorporation of expert evidence in Ireland - Beirne, Aoife Teresa (Trinity College (Dublin, Ireland). School of Law, 2017)
This thesis concerns the incorporation of expert evidence into Irish criminal and civil proceedings. The methodology employed in this thesis is doctrinal legal analysis. It is the product of extensive and detailed analysis of primary and secondary sources. The focus of the thesis is on Ireland. However, as the subject of expert evidence in Ireland is lacking in focused academic and judicial commentary, the thesis relies on a number of comparative sources to inform the legal analysis. While this thesis does not purport to be multidisciplinary, Chapters 4 and 5 concern scientific expert evidence and necessitated some understanding of scientific methods for the presentation of expert scientific evidence, as well as psychological models of jury comprehension
Keywords: Law, Ph.D.; PhD Trinity College Dublin, 2017